A novel single-stranded DNA detection method based on organic semiconductor heterojunction. (December 2016) - Gu, Wen; Liu, Hongbo; Zhang, Xia; Zhang, Hao; Chen, Xiong; Wang, Jun
Graphical abstract: Highlights: We developed a novel ssDNA detection method by using organic heterojunction. The conductivity and resistivity of the organic heterojunction film were extracted by transmission line model method. The electrical response of the device for ssDNA detection can be increased by reducing the upper CuPc layer. Abstract: We demonstrate a novel DNA detection method with low-cost and disposable advantages by utilizing F16 CuPc/CuPc planar organic heterojunction device. Single-stranded DNA (ssDNA) molecules have been well immobilized on the surface of CuPc film observed by atomic force microscopy, producing an obvious electrical response of the device. The conductivity of the organic heterojunction film was significantly increased by ssDNA immobilization because ssDNA molecules brought additional positive charges at heterojunction interface. Furthermore, the thickness dependence of CuPc upper layer on the electrical response was studied to optimize the sensitivity. This study will be helpful for the development of organic heterojunction based biosensors.